Research trends among new investigators at ISOQOL: a bibliometric analysis from 2019 to 2023 - Jae-Yung Kwon; Manraj N. Kaur; Ellen B. M. Elsman; Ava Mehdipour; Lori Suet Hang Lo; Ahmed M. Y. Osman; Sandrine Herbelet; Carrie-Anne Ng; Lotte van der Weijst; on behalf of the New Investigators Special Interest Group Members (Journal of Patient-Reported Outcomes)
Abstract Background New investigators (NI), encompassing graduate students, recent doctoral graduates, and early-career faculty, are instrumental in advancing quality of life (QoL) research through innovative methodologies and diverse perspectives. Within the International Society for Quality of Life Research (ISOQOL), the New Investigators Special Interest Group (NI-SIG) fosters collaboration and supports this community. This study utilizes bibliometric analysis to examine the contributions of NI-SIG members, focusing on publication trends, collaboration patterns, and thematic developments in QoL research. Methodology Data on publications authored by 56 NI-SIG members between 2019 and 2023 were extracted from Web of Science and Scopus. A two-step screening process, guided by the Wilson and Cleary model of QoL, identified 561 unique documents for analysis. Descriptive metrics included publication trends, citations, journal impact factors, and geographic distribution, while network analysis explored co-authorship patterns. Thematic mapping was conducted using clustering algorithms to identify established and emerging research areas. Results Publication output rose steadily from 2019 to 2022, peaking at 163 publications before declining to 135 in 2023, accompanied by a reduction in average citations per document from 4.8 to 1.3. The majority of publications appeared in leading journals such as Quality of Life Research (n = 128), Journal of Patient-Reported Outcomes (n = 17), and BMJ Open (n = 15). Geographic analysis revealed that most contributors were from high-income countries, with the United States, Canada, and Australia accounting for over 50% of publications. Co-authorship network analysis highlighted a robust, interconnected cluster of authors, though opportunities remain to enhance global partnerships, particularly with low- and middle-income countries. Thematic analysis identified well-established areas, including psychometric validation and cancer, alongside emerging topics such as mixed methods in QoL research. Conclusion This study highlights robust collaborations among NI-SIG members while identifying opportunities to enhance international collaboration and methodological innovation. Expanding partnerships with underrepresented regions and embracing advanced technologies such as natural language processing could foster inclusivity and drive transformative advancements in QoL measurement and application.